1991
DOI: 10.1093/jnci/83.10.712
|View full text |Cite
|
Sign up to set email alerts
|

Induction of nm23 Gene Expression in Human Colonic Neoplasms and Equal Expressions in Colon Tumors of High and Low Metastatic Potential

Abstract: Levels of expression of the murine nm23 gene inversely correlate with metastatic potential in several rodent tumor model systems. Expression of the human nm23 homologue also is lower in human breast cancers of high metastatic potential than in breast cancers of low metastatic potential. In the present study, we examined changes in nm23 expression during colon carcinogenesis as found in 18 matched pairs of normal and neoplastic human colon tissues. We found that a 0.8-kilo-base nm23 transcript was expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
65
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(72 citation statements)
references
References 0 publications
7
65
0
Order By: Relevance
“…No correlation to the tumour stage was described by Haut et al (1991), Myeroff andMarkowitz (1993), andZeng et al (1994);Yamaguchi et al (1993) presented a different view in a study.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…No correlation to the tumour stage was described by Haut et al (1991), Myeroff andMarkowitz (1993), andZeng et al (1994);Yamaguchi et al (1993) presented a different view in a study.…”
mentioning
confidence: 93%
“…Conflicting observations have been reported on the protein level (Ayhan et al, 1993;Haut et al, 1991;Lacombe et al, 1991;Royds et al, 1994;Tannapfel et al, 1995; Yamaguchi et al, 1993;Zeng et al, 1994); on the mRNA level (Haut et al, 1991;Myeroff and Markowitz, 1993; Yamaguchi et al, 1993;Zeng et al, 1994); and on the DNA-level (Bafico et al, 1993; Campo et al, 1994; Cawkwell et al, 1994;Cohn et al, 1991;Heide et al, 1994; lacopetta et al, 1994;Okada et al, 1994;Steeg et al, 1991;Wang et al, 1993;Whitelaw and Northover, 1994).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Among them, the nm23 gene, with potential tumor-suppressor function, had been reported to be negatively correlated with metastatic potential in certain spontaneous and experimental tumors (Barnes et al, 1990;. Recent con¯icting results, however, have revealed no signi®cant relationship between Nm23 expression and metastatic ability of colon cancer cells (Haut et al, 1988;Cohn et al, 1991;Myero and Markowitz, 1993;Wang et al, 1993;Whitelaw and Northover, 1993). DCC also seemed to be a candidate tumor suppressor gene, deletions and somatic mutation of which have been observed in a number of colorectal cancers (Fearon et al, 1990;Ookawa et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all of the above studies demonstrated a negative prognostic impact of nm23 overexpression or late T stage tumours (Zou et al, 1993;Müller et al, 1998). There were also some discrepancies among previous studies of the same tumours, such as gastric and colorectal cancers (Cohn et al, 1991;Haut et al, 1991;Kodera et al, 1994;Müller et al, 1998). Concerning gastric cancers, Kodera et al (1994) reported that a negative prognostic impact of decreased nm23 expression might correlated with increased lymphatic metastasis; while Müller et al (1998) showed nm23 overexpression was associated with aggressive tumour growth and poor survival.…”
Section: Discussionmentioning
confidence: 88%